Falls in Older people with Cataract, a longitudinal evalUation of impact and riSk: the FOCUS study protocol. Issue 4 (15th January 2014) - Keay, Lisa; Palagyi, Anna; McCluskey, Peter; Lamoureux, Ecosse; Pesudovs, Konrad; Lo, Serigne; Ivers, Rebecca; Boufous, Soufiane; Morlet, Nigel; Ng, Jonathon Q; Stapleton, Fiona; Fraser, Michelle; et al.
Abstract : Background: Falls result in >$1 billion in treatment, disability, lost output and mortality each year in Australia and people with cataract are at increased risk. Previous research is inconclusive; one large Australian study using linked hospital data found no protective effect of cataract surgery. We aim to examine the impact of cataract-related vision impairment on falls risk and the additional effects of delays in access to surgery, refractive management (type of spectacles and changes to spectacle prescription) and the resulting level of function, particularly binocular function which can impact balance. Method/design: A prospective, 24-month cohort study is planned involving over 700 patients aged 70 years or older with bilateral cataract presenting for surgery at five public hospital eye clinics in Sydney, Melbourne and Perth, Australia. The primary outcomes will be self-reported falls and falls requiring medical care, assessed objectively using administrative data sets. Secondary outcomes include community participation, quality of life, mood and depressive symptoms. McNemar's test will be used to evaluate differences in falls rate before, after first eye and after second eye cataract surgery. Generalised Estimating Equations linear regression analysis will be undertaken to examine factors associated with falls risk and the secondary outcomes. Discussion: With limited resources to further shorten public waiting lists, there is a need to better understand an individuals' risk of fall injury or other negative consequences while waiting for surgery. The findings of this project will inform the development of strategies to reduce falls risk in the many older people with cataract.